Portable Electric Fencing for Bear Deterrence and Conservation - Tom S. Smith; Bryan Hopkins; John Gookin; Samantha Thompson (Utah State University, 2018)
Although bear-inflicted (Ursus spp.) human fatalities are rare in North America, human injuries, property damage, and bear mortalities occur wherever bears and humans commingle. We investigated the efficacy of portable electric fencing systems for bear deterrence under a variety of environmental conditions in the lab and field. Our results showed that the bear deterrent systems we evaluated were effective in protecting humans, their food, and property from bears >99% of the time. Herein, we discuss the benefits of using electric fencing, reasons why fences sometimes fail, and provide guidance regarding the most effective implementation of the systems we evaluated. Lastly, we also explore why this deterrent is not yet in widespread use. We encourage the use of electric fencing in bear country for protecting humans, their camping gear and food, and ultimately to promote bear conservation.